Pengaruh Asam Cuka Terhadap Kandungan Histamin Dalam Daging Ikan Komu (Auxis rochei) - Hattu, Nikmans; Fransina, Eirene G.; Seumahu, Cecelia A.; Sopacua, Josina (Indonesian Journal of Chemical Research, 2016)
The research on the effect of vinegar to histamine content in bullet tuna (Auxis rochei) has been done. Histamine content of quantitatively determined using a standard curve regression equation (y = 0.005 x - 0.046) with a price coefficient of determination (R2 = 0.926) is close to unity. The results showed levels of histamine in bullet tuna marinated in vinegar with variation concentrations of 5%, 10%, 15%, 20%, and 25% within 10 minutes, are 25.9099; 20.0408; 18.9671; 18.7108 and 18.6336 mg/100g respectively. While the levels of histamine in bullet tuna marinated in 25% of vinegar with variation of 10 minutes, 20 minutes, and 30 minutes, are 18.6336; 16.0550; and 15.5246 mg/100g respectively.